2008
DOI: 10.1080/00015458.2008.11680239
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal Lipoma of the Ascending Colon as a Source of Massive Lower Gastro-intestinal Bleeding: a Case Report

Abstract: Colonic lipomas are relatively uncommon lesions. They have been documented as the source of massive low gastro-intestinal bleeding in only five previous reports in the English language literature. We report an extremely rare case of massive haemorrhage caused by an ascending colon submucosal lipoma and review the pathophysiology, diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…In 90% of cases, these are localized in submucosa but occasionally they extend into the muscularis propria, while up to 10% are subserosal. 5 Sometimes only one segment of intestine may be involved, known as segmental lipomatosis. Age of presentation is highly variable, ranging from neonatal period to seventh decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…In 90% of cases, these are localized in submucosa but occasionally they extend into the muscularis propria, while up to 10% are subserosal. 5 Sometimes only one segment of intestine may be involved, known as segmental lipomatosis. Age of presentation is highly variable, ranging from neonatal period to seventh decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…When intestinal lipomatosis reaches a larger size then the symptoms usually start 6. The most common manifestations are non-specific abdominal pain, constipation, diarrhoea and bleeding 4 6 7.…”
Section: Discussionmentioning
confidence: 99%
“…They become symptomatic in less than 30% of cases [4-6] and this usually occurs when they increase more than 2 or 3 cm in diameter [7,11]. It is reported that a 75% of patients with intestinal lipomas larger than 4 cm had symptoms [20].…”
Section: Presentationmentioning
confidence: 99%
“…This pain is usually repeated before the patient asks for medical assistance [1,3,4,6,7]. Constipation, altered bowel habits and hemorrhage are symptoms also often reported [4-6].…”
Section: Presentationmentioning
confidence: 99%
See 1 more Smart Citation